Do conditional cash transfers (CCT) raise educational attainment? A case study of Juntos in Peru - Anja Gaentzsch (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
This paper empirically investigates the impacts of Peru's Conditional Cash Transfer (CCT) programme JUNTOS upon educational outcomes of beneficiary children. The findings associate Juntos participation with higher overall enrolment rates and grades of schooling for children aged 12 to 18 years. This effect translates into a higher probability of finishing primary school and entering secondary school for the same age group. Evidence suggests that this is linked to a faster progression through grades rather than final years of schooling. We find no impact on enrolment or school progression for younger children aged 6 to 11 years. Further, Juntos participation does not have a positive impact upon scores of receptive vocabulary and mathematics tests. Rather, children aged 7-9 years seem to make less progress over time compared to children from non-beneficiary families, while there is no impact upon older children. Evidence on the underlying reasons for this is inconclusive and merits further analysis.
Keywords: I24; I25; I38; 330; conditional cash transfer; human capital investment; social assistance; educational attainment